Journal of Applied Informatics and Technology (Full Issue): Vol. 2 No. 1 (2020): January-June - Journal of Applied Informatics and Technology (Journal of Applied Informatics and Technology, 2023)
Contents - The Development of Geographic Information Systems for Crop Cultivation and Food Production and Agricultural Tourism in Phetchaburi Province (pp. 1-18) - Optimizing Document Retrieval by Measurement Resemblance Between Semantic Word Methods (pp. 19-29) - Traffic Less Navigation with Haversine Formula and RPA Algorithm (pp. 30-45) - Aquaman the Movie, Through the Lens of Feminists (pp. 46-56) - Marketing Communication Strategy Developing for Ban Yangilai and Ban Dongua Occupational Group, Ku Santarat Subdistrict, Mahasarakham District (pp. 57-76)